THE IMPLEMENTATION OF GUIDANCE SERVICES GROUP PLAY TECHNIQUE CAN ENHANCE STUDENTS' MOTIVATION IN CLASS X MAN PADANG YEAR STUDY 2014-2015 - Linda Fitria (Ristekdik : Jurnal Bimbingan dan Konseling, 2016)
The research is based on the problem of the low student motivation in the school environment and the general problem of this research is "How to increase student motivation through counseling services engineering group play" ?. Which is formulated as follows: (1) How student motivation before being given counseling services group playing techniques in experimental and control groups? (2) How student motivation is given after counseling services group playing techniques in experimental and control groups? (3) How is the effectiveness of guidance services group playing techniques to improve students' motivation ?. The goal is to obtain a picture of the increase in students' motivation in MAN Padang through group counseling services playing techniques. The method used in this research is True experimental design with shapes pretest-posttest control group design. With a sample of experimental class is a class of 10 students Xc and Xd control class is the class of 10 students so as the total sample of 20 students. Group counseling services are conducted three meetings, the first meeting prestest implement and execute all posttest.Data treatment were analyzed using the Wilcoxon rank test and kolgomorov signesd smirnov 2 with the help SPPS version 20.00. From the results of the implementation is done, a significant increase is mainly posttest eksperimen.Hasil findings in the experimental group and the control group there were significant increases between konrol posttest and posttest results of the experiment. The average variable students' motivation at 157.7000. (posttest experiment) while the control group 155.2000. (posttest control) is visible difference signifikan.Hasil processing of the data, indicate that the implementation of guidance services group play technique can enhance students' motivation in class X MAN Padang.